You are special - Lucado, Max (New York : Scholastic, 1997)
Eli the woodcarver helps Punchinello understand how special he is -no matter what other Wemmicks may think.
Grade 2
Keywords: Acceptance -- Fiction; Confidence -- Fiction; Children stories